Understanding earthquake physics through high frequency multiple point source inversion and earthquake cycle simulation - Shi, Qibin (Nanyang Technological University, 2021)
Deep insights to earthquake physics is crucial for seismic hazard assessment and mitigation. In this dissertation, my goal is to understand the fundamental earthquake source parameters and fault slip process and their relationship and interaction with geological structure, focusing on using kinematic earthquake rupture inversions and physics-based earthquake cycle simulations. To better resolve earthquake kinematic source processes at high frequency, we develop a novel multiple-point-source inversion scheme based on the Cut-and-Paste waveform modeling method and the path calibration approach. We apply this inversion scheme to representative crustal strike-slip earthquakes in Japan and the United States. We then apply it to the subduction zone megathrust earthquake in Alaska. Using this method, we robustly determine the kinematic features of the earthquake rupture processes including complex fault geometries, rupture propagation and rupture styles. Finally, we conduct earthquake cycle simulations to mimic highly diverse slip behaviours on the Nankai megathrust, including full and partial earthquake ruptures, long- and short-term slow slip, slow earthquakes and creep, in addition to the viscoelastic asthenosphere flow. We successfully reproduce the typical down-dip segmentation of slip behaviours that are controlled by the geological structure of the overriding plate and the complex interactions of the various slip behaviours during seismic cycles. My understanding of earthquake physics is greatly strengthened through this Ph.D. research.